Source identification of N2O produced during simulated wastewater treatment under different oxygen conditions using stable isotopic analysis - Azzaya, T; Toyoda, Sakae; Yoshida, Naohiro; Shiomi, Hiroshi; Kouno, Rina (Mongolian Journal of Chemistry, 2014)
Nitrous oxide (N2O), a potent greenhouse gas which is important in climate change, is predicted to be the most dominant ozone depleting substance. It is mainly produced by oxidation of hydroxylamine (NH2OH) or reduction of nitrite (NO2-) during microbiological processes such as nitrification and denitrification. Wastewater treatment plant (WWTP) is one of the anthropogenic N2O sources because inorganic and organic nitrogen compounds are converted to nitrate (NO3-, in the case of standard system) or N2 (in the case of advanced system) by bacterial nitrification and denitrification in WWTP. We investigated the N2O production mechanisms during batch experiments that simulate wastewater treatment with activated sludge under various dissolved oxygen (DO) concentrations by stable isotope analysis. About 125mL of water was sampled from 30L incubation chamber for several times during the incubation, and concentration and isotopomer ratios of N2O and N-containing species were measured using gas chromatography/isotope ratio mass spectrometry (GC/IRMS). Ammonium (NH4+) consumption was accompanied by increment of nitrite (NO2-), and at the same time dissolved N2O concentration gradually increased to 4850 and 5650 nmol kg-1, respectively, during the four-hour incubation when DO concentrations were 0.2 and 0.5 mg L-1. Observed low SP values (0.2-8.9‰ at DO-0.2 mg L-1, -5.3-6.3‰ at DO-0.5 mg L-1, -1.0-8.3‰ at DO-0.8 mg L-1) in N2O and relationship of nitrogen isotope ratios between N2O and its potential substrates (NH4+, NO3-) suggested that N2O produced under the aerobic condition derived mainly from NO2- reduction by ammonia-oxidizing bacteria (nitrifier–denitrification). DOI: http://doi.dx.org/10.5564/mjc.v15i0.313 Mongolian Journal of Chemistry 15 (41), 2014, p4-10